26. ASSESSING QUALITY OF LIFE OF THE INTERVENTION MODEL “HEALTHY AGEING” IN CHI LINH, HAI DUONG AND KIM BOI, HOA BINH DURING 2018-2021 (Vietnam Journal of Community Medicine, 2023)
Introduction: Vietnam is on the cusp of a dramatic aging of the population. In 2015, Vietnam became an aging society. But elderly Vietnamese struggle with multiple diseases and a short healthy lifespan. Objective: This paper aimed to assess the change in the quality of life of the elderly before and after the intervention applying the "Healthy Ageing" model (period 2018-2021) in 4 communes of Chi Linh City, Hai Duong and Kim Boi district, Hoa Binh. Methods: The study used a quasi-experimental design that used data before and after an intervention to evaluate the effectiveness of the intervention. The total number of elderly participants was 1260 people with 2 data collection periods: Jan-Apr, 2018 and Jan-Apr, 2022. Findings: The results showed that quality of life scores ranged from 5.96 to 8.09, with the overall score in the intervention group (7.20) significantly higher than in the control group (6.96).Conclusions: The intervention model “Healthy ageing” showed its effectiveness in improving quality of life amongst elderly.
Keywords: Elderly, intervention, healthy aging, quality of life, Chi Linh, Kim Boi.